2020
DOI: 10.1002/eng2.12227
|View full text |Cite
|
Sign up to set email alerts
|

The influence of pain on tibiofemoral joint contact force and muscle forces in knee osteoarthritis patients during stair ascent

Abstract: This study investigated the tibiofemoral joint (TFJ) forces and supporting muscle forces displayed by knee osteoarthritis (OA) patients during stair ascent, and if these forces were influenced by the presence of pain. Fifteen knee OA patients partitioned into two groups based on pain experienced during stair ascent trails using a Visual Analogue Scale (VAS) (OA-pain = 10; OA-no pain = 5) and 14 healthy aged-matched controls took part in this study. Kinematic and kinetic data were collected during three stair a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Previous research on medial-lateral KCF distribution in OA subjects via musculoskeletal modeling showed mean MFRatio ranging from 63% to 87% on the force peak during walking ( Kumar et al, 2013 ; Sritharan et al, 2017 ; Van Rossom et al, 2018 ; Zeighami et al, 2021 ), which is in agreement with our findings (i.e., MFRatio of 75%). In addition, we found agreement on the different medial-lateral KCF distribution during stair ascending with a previous study showing MFRatio slightly below 50% especially on the force peak in 10 symptomatic OA subjects ( Price et al, 2020 ). Conversely, our findings differed from those of the other study analyzing stair negotiation ( Meireles et al, 2019 ), where the authors found MCFs larger than LCFs on the force peak of stair ascending and descending.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous research on medial-lateral KCF distribution in OA subjects via musculoskeletal modeling showed mean MFRatio ranging from 63% to 87% on the force peak during walking ( Kumar et al, 2013 ; Sritharan et al, 2017 ; Van Rossom et al, 2018 ; Zeighami et al, 2021 ), which is in agreement with our findings (i.e., MFRatio of 75%). In addition, we found agreement on the different medial-lateral KCF distribution during stair ascending with a previous study showing MFRatio slightly below 50% especially on the force peak in 10 symptomatic OA subjects ( Price et al, 2020 ). Conversely, our findings differed from those of the other study analyzing stair negotiation ( Meireles et al, 2019 ), where the authors found MCFs larger than LCFs on the force peak of stair ascending and descending.…”
Section: Discussionsupporting
confidence: 91%
“…In summary, most studies calculating KCFs and their distribution involve subjects with total knee replacement, there are limited and controversial data on healthy and OA subjects with limited sample sizes, and the few studies analyzing activities different from walking, such as stair ascent and descent, did not include the effect of the anatomical parameters ( Meireles et al, 2019 ; Price et al, 2020 ). Therefore, it is unclear how variable are KCFs and their distribution when the personalized anatomical parameters are considered during different activities in knee OA subjects, and so is the consequent relationship between KCF distribution and the anatomical parameters.…”
Section: Introductionmentioning
confidence: 99%